References of the New Theory of Trade and Economic Growth - Spiridon Pralea (CES Working Papers, 2012)
This paper shows that the dynamization of the traditional theory of international trade through the study of growth effects on the foreign trade in the framework of neoclassical analysis, alongside the approach with the Keynesian toolkit of the role of foreign trade as a factor of growth, have constituted the main aspects of the new theory of trade and economic growth. The “new theory” basically represents a set of theories and models of the type “growth-led export” or “export-led growth”, which explain the complex role of foreign trade in the dynamic of development, the new segments of international trade, and also provides base for trade strategies for development. Their typology includes: “import-substitution strategy”, “export-promotion strategy”, and more recently “outward oriented strategy”. In the context of regionalization and globalization of competition the author believes most appropriate the states' option for a “outward - oriented competitive development strategy”.
Keywords: F1; O11; O4; 330; foreign trade; economic growth; trade strategies for development Romania